Analysis & development of automated system for on-wafer channel thermal measurement of RF power devices using ordinary lab instruments. (April 2021) - Ali, Anwar; Ali, Haider; Pirola, Marco; Tong, Jijun
Highlights: Experimental setup was developed using inexpensive ordinary lab instruments. The setup measures the channel temperature of RF devices using ΔVgs technique. Channel parameters i.e. thermal resistance ( θth ) is found and ( Cth ) associated model is proposed for extraction. The proposed technique is applied on three HEMT devices with same dimensions. The results were similar for all three devices which reflect accuracy of the technique. Abstract: Accurate and precise measurement of channel temperature for RF devices and especially for high power density devices such as MESFETs and GaAs High Electron Mobility Transistors (HEMTs) is essential for understanding the physics behind device degradation. In high power density devices, self-heating effects (SHEs) and channel to base plate temperature gradients are very high. This paper proposes an automated experimental setup using ordinary lab instruments for the measurement of channel temperature of MESFETs and HEMTs in terms of thermal resistance ( θth ) and thermal capacitance ( Cth ). The automated experimental setups utilize ordinary lab equipment instead of using specialized high-end tools. With ambient temperature, DC bias conditions, and RF power levels, channel temperature is calculated using θth and Cth parameters. The proposed technique is applied on three different HEMTs and the results were similar for all of them which reflect accuracy of the technique.